2011
DOI: 10.1353/ken.2011.0007
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Risk-Benefit Evaluations in Biomedical Research

Abstract: Essentially all guidelines and regulations require that biomedical research studies have an acceptable risk-benefit profile. However, these documents offer little concrete guidance for implementing this requirement and determining when it is satisfied. As a result, those charged with risk-benefit evaluations currently assess the risk-benefit profile of biomedical research studies in unsystematic ways, raising concern that some research participants are not being protected from excessive risks and that some val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 61 publications
0
110
0
1
Order By: Relevance
“…The use of placebo controls must therefore be scrutinized like most other research procedures. This implies -consistent with the earlier-mentioned criteria for acceptable placebo use -that the risks of withholding or delaying an established effective intervention must be minimized and justified in relation to the potential clinical benefits to participants and/ or the scientific and social value of the knowledge to be gained from the research Brody, 2003, 2007;Rid and Wendler, 2011).…”
Section: 'Acceptable' Risk From Withholding Treatmentmentioning
confidence: 61%
“…The use of placebo controls must therefore be scrutinized like most other research procedures. This implies -consistent with the earlier-mentioned criteria for acceptable placebo use -that the risks of withholding or delaying an established effective intervention must be minimized and justified in relation to the potential clinical benefits to participants and/ or the scientific and social value of the knowledge to be gained from the research Brody, 2003, 2007;Rid and Wendler, 2011).…”
Section: 'Acceptable' Risk From Withholding Treatmentmentioning
confidence: 61%
“…9,12,[14][15][16] Definitions and meanings of risk vary, however, and understanding these in terms of hazard, exposure, consequence and probability is complex. 6 In this study, we identified three major differences in perspectives about risk between HCPs and ISCIs.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, risk is a complex concept with different meanings, definitions and layers. 5,6 Academic papers dissect risks according to different definitions, phrasing risks in terms of an unwanted event, the cause of an unwanted event or a probability formula. 7,8 They analyze risks within levels of uncertainty, 9,10 and consider, on a theoretical level, and without reference to a practical definition, which risks would be acceptable to the SCI population on micro, meso and macro levels.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is important for many kinds of laboratory research, but in addition it has potential technological applications in such diverse fields as medicine, agriculture, and industry. Indeed, recombinant DNA methods are already being employed to produce medically important hormones, such as insulin and human growth hormone 23 .…”
Section: Scientific Freedom In Research At the Molecular Levelmentioning
confidence: 99%